The Effect of Leadership Style and Employee Engagement on Generation Z Job Satisfaction in The Property Industry in Jakarta with Employee Resilience as A Mediation Variable - Aris Muhamad Syukur; Corry Yohana; Christian Wiradendi Wolor (PT. Publikasiku Academic Solution, 2026)
Generation Z has become an increasingly important component of the workforce, yet many young employees experience challenges related to job satisfaction, leadership expectations, and workplace adaptation. In the property industry, which is characterized by dynamic market conditions and high work demands, understanding the factors that influence Generation Z employees’ job satisfaction is essential. This study aims to examine the effect of leadership style and employee engagement on Generation Z job satisfaction, with employee resilience as a mediating variable in the property industry in Jakarta. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 240 Generation Z employees working in property companies in Jakarta. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that leadership style and employee engagement have a positive and significant effect on employee resilience. Furthermore, leadership style, employee engagement, and employee resilience significantly influence job satisfaction. Employee resilience has the strongest direct effect on job satisfaction and significantly mediates the relationship between leadership style and employee engagement toward job satisfaction. These findings highlight that psychological resilience plays a crucial role in strengthening employees’ ability to adapt and maintain satisfaction in demanding work environments. Therefore, organizations should develop supportive leadership practices and strengthen employee engagement programs to enhance resilience and job satisfaction among Generation Z employees.